2022
DOI: 10.3390/ijms23073812
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of the Antidepressants Fluoxetine and Fluvoxamine in the Treatment of COVID-19

Abstract: Mapping non-canonical cellular pathways affected by approved medications can accelerate drug repurposing efforts, which are crucial in situations with a global impact such as the COVID-19 pandemic. Fluoxetine and fluvoxamine are well-established and widely-used antidepressive agents that act as serotonin reuptake inhibitors (SSRI-s). Interestingly, these drugs have been reported earlier to act as lysosomotropic agents, inhibitors of acid sphingomyelinase in the lysosomes, and as ligands of sigma-1 receptors, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 105 publications
0
22
0
Order By: Relevance
“…In this context, "not prescribed" fluvoxamine implies being prescribed with some other treatment for the underlying psychiatric condition, and the contrast between "prescribed" and "non-prescribed" patients regarding COVID-19 outcomes would be informative about fluvoxamine only if "not prescribed fluvoxamine" means also "not being treated for COVID-19" in the sense implied for fluvoxamine. Fluoxetine is another serotonine selective reuptake inhibitor (SSRI) that shows some antiviral and anti-inflammatory activity in non-clinical models 9 . One observational study 10 included laboratory confirmed COVID-19 adult outpatients in the pre-vaccination era: a cohort of patients prescribed fluoxetine (n=470) at a critical peridiagnostic period were matched (propensity-score based, 1:15) to patients not prescribed any SSRI or a related treatment (i.e., vilazodone, vortioxetine) -and yielded a relatively 25% lower mortality.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, "not prescribed" fluvoxamine implies being prescribed with some other treatment for the underlying psychiatric condition, and the contrast between "prescribed" and "non-prescribed" patients regarding COVID-19 outcomes would be informative about fluvoxamine only if "not prescribed fluvoxamine" means also "not being treated for COVID-19" in the sense implied for fluvoxamine. Fluoxetine is another serotonine selective reuptake inhibitor (SSRI) that shows some antiviral and anti-inflammatory activity in non-clinical models 9 . One observational study 10 included laboratory confirmed COVID-19 adult outpatients in the pre-vaccination era: a cohort of patients prescribed fluoxetine (n=470) at a critical peridiagnostic period were matched (propensity-score based, 1:15) to patients not prescribed any SSRI or a related treatment (i.e., vilazodone, vortioxetine) -and yielded a relatively 25% lower mortality.…”
Section: Introductionmentioning
confidence: 99%
“…People suffering conditions requiring antidepressant/anxiolytic treatment not treated with fluvoxamine are likely exposed to other treatments. Biological (mechanistic) rationale to support their use in COVID-19 has been argued for a range of antidepressants/anxiolytics not only for SSRIs [8,9], with, seemingly, an emphasis on fluvoxamine and fluoxetine [15]. One early observational study based on administrative data on COVID-19 patients identfied based on the fact of emergency department vistis of hospitalizations suggested that those prescribed fluoxetine (n=470) had by 28% lower mortality than propensity score-matched controls not prescribed with any SSRI [16].…”
Section: Introductionmentioning
confidence: 99%
“…The articles included in this Special Issue are focused on prevention, diagnostics, signatures of the disease course, molecules involved, vaccine-related adverse effects, potential treatments, and short- and long-term consequences. There are 3 original research papers [ 2 , 3 , 4 ] and 11 review articles [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
mentioning
confidence: 99%
“…Paulina Niedźwiedzka-Rystwej and colleagues [ 5 ] discuss whether the cytokine storm results from immune system suppression or if it is a positive reaction necessary to clear the virus from the infected organism. The hope of finding new drugs acting against COVID-19 is sustained by the article by Mahdi et al [ 6 ] who present an overview of fluoxetine and fluvoxamine regarding their use in COVID-19. The two drugs are antidepressive agents that were also reported to act as lysosomotropic agents, inhibitors of acid sphingomyelinase in the lysosomes, and ligands of sigma-1 receptors.…”
mentioning
confidence: 99%